The Narcotic Farm - Campbell, Nancy D. (Abrams, 2008)
Introduction -- A new deal -- Competent and humane -- The two roads to Narco -- The Lexington cure -- The fantastic lodge -- The talking cure -- Down on the farm -- Work is therapy -- At play in the fields of Narco -- The greatest band you never heard -- The addiction research center -- The revolving door